Spotlight on ORNAC Members: An Interview With Barbara Mushayandebvu RN, CPN(C), ORNAC President - Dow, Heather (Operating Room Nurses Association of Canada Journal, 2018)
Barbara Mushayandebvu has been a Registered Nurse in the OR since 1985. She has worked in several OR environments in Zimbabwe, South Africa, the UK, and Canada and so brings a global perspective to the ORNAC Board. After 14 years at the Peter Lougheed Centre in Calgary she moved to Ottawa for 2 years, where she worked at both the Queensway Carlton Hospital and the Civic Campus of The Ottawa Hospital, and has recently returned to Calgary and Peter Lougheed Centre. Barbara has experience in all surgical specialties and has worked as a Clinical Leader and Clinical Nurse Educator. Barb served as ORNAA president from 2010 to 2012, ORNAC Journal Editorial Chair from 2009 to 2015, the ORNAC Board member representing Alberta from 2009 to 2012, and was Co-Chair of the 2015 ORNAC National Conference, and is currently serving as ORNAC President (2017-2019). Barb has been happily married to Martin, for 33 years, and they have 2 beautiful daughters. The three of them are her rocks and anchors and she wouldn’t know what to do without their love and support.